2021
DOI: 10.1016/j.heliyon.2021.e07070
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stillbirth in hospitals of North Shoa Zone, Oromia region, Central Ethiopia: A case control study

Abstract: Background: World Health Organization defined stillbirth as birth of fetus at 28 weeks or above gestation with a birth weight of 1000 g or body length of 35 cm. Majority of stillbirths occur in low and middle income nations. Efforts made in Ethiopia to improve maternal and child health are showing encouraging results, even though the magnitude didn't reach the expected level. Identification of determinants of stillbirth is quite substantial to apply further meaningful actions. Objective: To assess the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
4
1
0
Order By: Relevance
“…This study also revealed that induced labor onset was also a significant factor associated with an increased risk of stillbirth. This finding is supported by a previous study [ 31 ]. The possible explanation for this association is that when labor is induced, the fetus may be exposed to stressful uterine contractions, which can ultimately lead to fetal demise [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also revealed that induced labor onset was also a significant factor associated with an increased risk of stillbirth. This finding is supported by a previous study [ 31 ]. The possible explanation for this association is that when labor is induced, the fetus may be exposed to stressful uterine contractions, which can ultimately lead to fetal demise [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this study identified that women with a labor duration of 24 hours or longer were 3.80 times more likely to experience stillbirth. This finding aligns with the results of various studies conducted in Ethiopia [ 31 33 ], which consistently reported prolonged labor as a significant risk factor for stillbirth. The prolonged labor may result in fetal distress, leading to intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 91%
“…The study has also revealed that congenital malformations, deformations, and chromosomal abnormalities were associated with stillbirth outcomes, i.e., there is a threefold higher risk of stillbirth among perinate with congenital abnormalities than their counterparts. This finding was consistent with studies conducted in Ethiopia ( 71 ), Cameroon ( 28 ), and India ( 26 ). This could be due to a lack of maturity of the vital organs for fetal survival making the fetus prone to fatal complications and death.…”
Section: Discussionsupporting
confidence: 92%
“…Congenital malformations, deformations, and chromosomal abnormalities were also positively related to the three-timing of perinatal deaths. The finding was coherent with studies conducted in Ethiopia (Bahardar and North Shewa) [ 71 , 106 ] Cameroon [ 107 ], India [ 33 ], and Jordan [ 108 ]. This could be explained by the organ dysfunction as well as the lack of vital organs used for the survival of the fetus making them more vulnerable to fatal complications.…”
Section: Discussionsupporting
confidence: 87%